2011
DOI: 10.1007/s00330-011-2249-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced magnetic resonance imaging with Gd-EOB-DTPA for the evaluation of liver fibrosis in chronic hepatitis patients

Abstract: DCE-MRI with Gd-EOB-DTPA is a noninvasive imaging, by which multiple perfusion parameters can be measured to evaluate the severity of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 36 publications
(43 reference statements)
6
93
0
Order By: Relevance
“…These studies also provided hepatic function maps to depict the anatomic distribution of hepatic function. A more recent study adopting a dual-input single compartment model suggested that the arterial blood flow was a good predictor for mild fibrosis [44]. …”
Section: Hepatic Function From Hepatic Parenchymal Enhancementmentioning
confidence: 99%
“…These studies also provided hepatic function maps to depict the anatomic distribution of hepatic function. A more recent study adopting a dual-input single compartment model suggested that the arterial blood flow was a good predictor for mild fibrosis [44]. …”
Section: Hepatic Function From Hepatic Parenchymal Enhancementmentioning
confidence: 99%
“…Chen et al performed a prospective study using Gd-EOB-DTPA in patients with chronic hepatitis to calculate perfusion parameters by applying a dual-input single compartment model. They found a significant increase in arterial perfusion at 60 s and 100 s in patients compared with healthy subjects and a significant difference in arterial perfusion when three different fibrotic subgroups (none, mild and advanced) were compared at 60 s [113].…”
Section: Mr Elastographymentioning
confidence: 98%
“…In terms of diagnosis, malignant liver tumors have been reported to have high perfusion values (high blood flow, high blood volume, high permeability, and low mean transit time) compared with normal tissue [11,12]. In terms of treatment monitoring, HCCs show a fall in blood flow, blood volume, and permeability after antiangiogenic treatment or chemoembolization [13,14].…”
Section: Perfusion Imagingmentioning
confidence: 99%
“…In addition, new contrast agents and elastography are now being developed to increase the effectiveness of detection and characterization of tumors [3,11]. Furthermore, research into functional imaging such as perfusion imaging with CT or MRI, diffusion-weighted imaging (DWI), and elastography is making progress [12][13][14][15][16]. These techniques seem to have strong potential to improve detection and characterization of HCC [17,18].…”
Section: Introductionmentioning
confidence: 99%